2020
DOI: 10.5194/acp-2020-894
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PM<sub>1</sub> composition and source apportionment at two sites in Delhi, India across multiple seasons

Abstract: Abstract. Air pollution in urban environments has been shown to have a negative impact on air quality and human health, particularly in megacities. Over recent decades, Delhi, India has suffered high atmospheric pollution, with significant particulate matter (PM) concentrations as result of anthropogenic activities. Organic aerosols (OA) are composed of thousands of different chemical species and are one of the main constituents of submicron particles. However, quantitative knowledge of OA composition, their s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…This was mainly due to the contraction of the boundary layer during the night and early hours of the morning being more pronounced which removes possible afternoon peaks 240 from specific sources, e.g. lunch hour cooking activities (Nakoudi et al, 2019;Reyes-Villegas et al, 2020). The pre-monsoon and monsoon diurnal cycles show species concentrations, excluding nitrate and chloride, were less affected by the higher boundary layer in the afternoon.…”
Section: Inorganic and Organic Pm Concentrationsmentioning
confidence: 96%
See 1 more Smart Citation
“…This was mainly due to the contraction of the boundary layer during the night and early hours of the morning being more pronounced which removes possible afternoon peaks 240 from specific sources, e.g. lunch hour cooking activities (Nakoudi et al, 2019;Reyes-Villegas et al, 2020). The pre-monsoon and monsoon diurnal cycles show species concentrations, excluding nitrate and chloride, were less affected by the higher boundary layer in the afternoon.…”
Section: Inorganic and Organic Pm Concentrationsmentioning
confidence: 96%
“…The AMS measurements were compared to a number of co-located instruments including black carbon (BC) measurements which were taken using an Aethalometer AE-31 and corrected for by a Single Particle Soot Photometer (SP-2; Droplet Measurement Technology, Boulder, CO) (Reyes-Villegas et al, 2020). Volatile 165 organic compounds (VOC) were measured using a high-resolution proton transfer reaction mass spectrometer (PTR-QiTOF, Ionicon Analytik G.m.b.H., Innsbruck, Austria).…”
mentioning
confidence: 99%
“…Figures 1a and 1b show the temporal variation of mass concentration of PM 2.5 species (Org, NO 3 , SO 4 , NH 4 , Chl, and BC), C‐PM 2.5 (composition‐based estimate of PM 2.5 calculated as the sum of NR‐PM 2.5 and BC) and relative contribution of species to the total PM 2.5 at HK and PF site. C‐PM 2.5 based on AMS and aethalometer measurements has been used in the previous studies as a representation of PM 2.5 concentrations (Gani et al., 2019; Reyes‐Villegas et al., 2021). For the total campaign period, the mean C‐PM 2.5 concentration at HK was 82.0 ± 48.1 μg m −3 (7.5–225.3) whereas 105.7 ± 52.5 μg m −3 (14.2–235.1) at HK and PF, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…These compounds have not been identified in published AMS spectra; however, many have pub- lished amine peaks within factors. Most studies name these factors nitrogen organic aerosol (NOA); however, some relate to specific local organic aerosol (LOA) (Aiken et al, 2009;Docherty et al, 2011;Sun et al, 2011;Saarikoski et al, 2012;Hayes et al, 2013;Bottenus et al, 2018;Zhang et al, 2018 ), and it is therefore suggested that this factor may also contain nitrile compounds.…”
Section: Elemental Analysismentioning
confidence: 99%